2014
DOI: 10.1080/00036846.2014.950836
|View full text |Cite
|
Sign up to set email alerts
|

Does distance matter for institutional delivery in rural India?

Abstract: This article estimates the causal effect of distance to health facility on in-facility birth in rural India, taking into account the endogenous placement of the health facility. We find that women living farther away from the health facilities are less likely to give birth at a health facility. Each additional kilometre from the nearest health facility is associated with a 4.4% decline in the probability of in-facility birth. Policy simulation results indicate that providing access to a health facility within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 31 publications
4
58
0
Order By: Relevance
“…One of these studies also identified decreased odds of institutional delivery among those who had to travel >10 km (Feyissa and Genemo 2014). Likewise, a 2014 study in rural India reported a 4.4% decrease in the probability of institutional delivery for each additional kilometer to the closest health facility (Kumar et al 2014). Other recent studies have reported similar findings (Gabrysch et al 2011;Mwaliko et al 2014).…”
Section: Discussionsupporting
confidence: 64%
“…One of these studies also identified decreased odds of institutional delivery among those who had to travel >10 km (Feyissa and Genemo 2014). Likewise, a 2014 study in rural India reported a 4.4% decrease in the probability of institutional delivery for each additional kilometer to the closest health facility (Kumar et al 2014). Other recent studies have reported similar findings (Gabrysch et al 2011;Mwaliko et al 2014).…”
Section: Discussionsupporting
confidence: 64%
“…Women who travelled less than one hour walking distance to a nearby health facility were 3 times more likely to deliver at a health institution than women who spent more than 1 hour to access a health facility. Similarly, studies in low income countries such as Bahi District, Central Tanzania, Rural Zambia, Nepal, Rural Malawi and Rural India 25,[28][29][30][31][32][33] showed that physical distance is one of the major constraints that prevented community members from accessing and using trained attendants and institutional deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary for this unfounded belief to be addressed via educational campaigns, since many young animals still remain at risk for months, even while the vaccine has been proven to be both safe and effective in puppies [47]. The deterrent effect of distance on attendance to healthcare facilities has been previously reported [48,49], in addition to the specific effect of distance on attendance to static vaccination clinics [12,44]. However, in this study, the effect of distance on absolute coverage was found to be insignificant.…”
Section: Variablementioning
confidence: 99%